2021
DOI: 10.1097/mco.0000000000000809
|View full text |Cite
|
Sign up to set email alerts
|

HMB and leucine supplementation during critical illness and recovery

Abstract: Purpose of reviewSkeletal muscle wasting is a serious consequence of critical illness, which may impact on long term physical and functional disability. To date, no intervention has been proven to reduce skeletal muscle wasting. Leucine and it's metabolite b-hydroxy-b-methylbutyrate (HMB) have been proposed as interventions. This review details the mechanism of action of both leucine and HMB, discusses the most recent research for both leucine and HMB and lastly discusses considerations for future research. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
(32 reference statements)
0
10
0
Order By: Relevance
“…The branched chain amino acid leucine is one of the most potent stimulators of muscle protein synthesis and acts via stimulation of the mammalian target of rapamycin (mTOR) pathway [42 ▪ ]. Its metabolite, β-hydroxy-β-methylbutyrate (HMB), also stimulates muscle synthesis via the mTOR pathway but, in addition, attenuates proteasome pathways that lead to muscle protein catabolism.…”
Section: Whole Protein or Individual Amino Acids?mentioning
confidence: 99%
“…The branched chain amino acid leucine is one of the most potent stimulators of muscle protein synthesis and acts via stimulation of the mammalian target of rapamycin (mTOR) pathway [42 ▪ ]. Its metabolite, β-hydroxy-β-methylbutyrate (HMB), also stimulates muscle synthesis via the mTOR pathway but, in addition, attenuates proteasome pathways that lead to muscle protein catabolism.…”
Section: Whole Protein or Individual Amino Acids?mentioning
confidence: 99%
“…Experiments with transaminase inhibitors have shown that the leucine effect on protein catabolism also partially depends on its degradation into KIC; however, the exact mechanism of this KIC effect is unknown. It should be noted that HMB, derived from KIC, is also an activator of protein synthesis and an inhibitor of muscle proteolysis, which has led to its proposed use in the treatment of muscle wasting in situations such as cancer cachexia, sarcopenia of aging, or critically ill patients [ 36 ]. However, its endogenous synthesis is far too low to contribute to the effects of leucine.…”
Section: Metabolic Properties Of Bcaas/bckasmentioning
confidence: 99%
“…This finding, however, needs confirmation in prospective randomized interventional trials. During the critically ill period, supplements like leucine and its metabolite β-hydroxy-β-methylbutyrate (HMB) have also been shown to positively impact long-term outcome and recovery [31].…”
Section: Feeding Strategy and Nutritional Support In The Recovery Pha...mentioning
confidence: 99%